Hubungan Kontrol Diri dengan Perilaku Menyontek pada Mahasiswa di Kota Makassar - Fira Zalsabila; Asniar Khumas; Andi Nasrawaty Hamid (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
The purpose of this study was to determine the relationship between self-control and cheating behavior in students in Makassar City. This study uses quantitative methods. The population in this study were students in Makassar City. The sampling technique used in this study was accidental sampling with the number of respondents as many as 225 (N = 225) students. This study was measured using a cheating behavior scale and a self-control scale. The research data were analyzed using the Spearman Rank Correlation Coefficient. The results of this study indicate that the significant value is p = 0.000 (p<0.05), and the correlation coefficient is r = -0.742. Thus, there is a relationship between self-control and cheating behavior in students in Makassar City. The correlation coefficient value shows a negative value, which means that self-control and cheating behavior are negatively correlated with each other and are in the high category.